2013
DOI: 10.1186/1749-8104-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Neurosensory development and cell fate determination in the human cochlea

Abstract: BackgroundHearing depends on correct functioning of the cochlear hair cells, and their innervation by spiral ganglion neurons. Most of the insight into the embryological and molecular development of this sensory system has been derived from animal studies. In contrast, little is known about the molecular expression patterns and dynamics of signaling molecules during normal fetal development of the human cochlea. In this study, we investigated the onset of hair cell differentiation and innervation in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 38 publications
(57 reference statements)
5
84
1
Order By: Relevance
“…3(B)]. We recently observed additional expression throughout the human fetal cochlear duct epithelium (Locher et al, 2013) and in all peripheral glial cells (Locher et al, 2014). Although it is likely that melanocytes play a major role in SNHL in WS or KS due to SOX10 mutations, it cannot be excluded that other SOX10+ cell types in the cochlea are involved as well.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…3(B)]. We recently observed additional expression throughout the human fetal cochlear duct epithelium (Locher et al, 2013) and in all peripheral glial cells (Locher et al, 2014). Although it is likely that melanocytes play a major role in SNHL in WS or KS due to SOX10 mutations, it cannot be excluded that other SOX10+ cell types in the cochlea are involved as well.…”
Section: Discussionmentioning
confidence: 90%
“…This implies that the endocochlear potential cannot be generated at this stage and, therefore, that the human fetus at W18 is still unable to hear. Although W20 has been proposed by us (Locher et al, 2013; Locher et al, 2014) and others (Pujol et al, 1991; Pujol and Lavigne‐Rebillard, 1995; Bibas et al, 2008) as the onset of human hearing based on the maturation of the organ of Corti and the cochlear nerve, it is more likely that hearing commences a few weeks later, which is in line with otoacoustic emission measurements (Chabert et al, 2006) and auditory brainstem responses in preterm infants (Lary et al, 1985; van Straaten et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CX26 and CX30 form heteromeric and heterotypic channels in most of the cochlear gap junction plaques (GJPs) (Sun et al., 2005) and in in vitro experiments (Yum et al., 2007). Recently, expression of various transcription factors and other proteins in human developmental fetal cochleae from gestational weeks 9–22 were investigated using immunohistochemistry (Locher et al., 2013, Locher et al., 2014), and it has been found that the expression of CX26 and CX30 is detectable in the outer sulcus cells at 18 weeks of gestation (Locher et al., 2015). …”
Section: Introductionmentioning
confidence: 99%